АРТЕРИОВЕНОЗНЫЕ ПОРОКИ ВЕНЫ ГАЛЕНА У НОВОРОЖДЕННЫХ - Иванов, Алексей Юрьевич; Комиссаров, Михаил Игоречич; Алешин, Иван Юрьевич; Усенко, Иван Николаевич; Тризна, Евгений Владимирович; Зеленин, Назар Мартович; Милашенко, Татьяна Владимировна; Яковлев, Алексей Владимирович; Купатадзе, Дмитрий Дмитриевич; Иванов, Дмитрий Олегович (FORCIPE, 2022)